(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The rapid development of artificial intelligence (AI) technologies has significantly expanded their application in medical imaging, including ultrasound diagnostics in gynecology. Ultrasound examination remains one of the most widely used, accessible, and non-invasive diagnostic methods for evaluating gynecological conditions; however, its effectiveness largely depends on the operator’s experience and subjective interpretation. The integration of AI-based algorithms offers new opportunities to improve diagnostic accuracy, standardize image interpretation, and reduce inter-observer variability. This article explores the prospects of applying artificial intelligence in the interpretation of gynecological ultrasound images, focusing on its potential role in the detection of benign and malignant pathologies, assessment of reproductive organs, and support of clinical decision-making. The advantages, current limitations, and future directions of AI-assisted ultrasound diagnostics in gynecology are discussed, highlighting its significance for improving diagnostic efficiency and patient outcomes.